Grandmothers and grandchildren in front of new technologies in Brazil and Portugal (Research, Society and Development, 2020)
Two of the outstanding characteristics of society in the 21st century have been the progressive increase in the elderly population and the increasingly intense advance of information and communication technologies. This study aimed to present an integrative review of the scientific literature on the theme of the relationship between grandparents and grandchildren in the face of new technologies in Brazil and Portugal, seeking to learn about information technologies for grandchildren and grandparents; describe the relationship of grandparents who accompany the growth of grandchildren through the virtual space; and identify the perception of grandchildren in relation to the behavior of grandparents as to new technologies. It was used articles published in sources of impact in order to enable a greater direction of research on this theme and discuss the trends pointed out by these publications as well as the production prospects in the area. Articles indexed were selected from data base nationals and internationals, from 2011 to 2019. It was observed that the use of these tools turns possible approximation and promotes affective relationships and solidarity between the two generations; provides the acquisition of basic skills for interaction / communication; it develops cooperation and trust, which makes this relationship stronger over time due to proximity and complicity between family actors, who dialogue in cyberspace and strengthen affective and intergenerational ties.